2018
DOI: 10.1002/adma.201803072
|View full text |Cite
|
Sign up to set email alerts
|

Localized Self‐Growth of Reconfigurable Architectures Induced by a Femtosecond Laser on a Shape‐Memory Polymer

Abstract: natural behavior, many works have been done to realize reconfigurable shape transformation with artificial soft materials in a controlled manner. [8][9][10][11] Heterogeneous structures composited of hydrogel constituents with different swelling/shrinkage ratio [12][13][14][15][16] or anisotropic swelling behavior [17,18] have been constructed to accomplish dynamic tunable morphologies. Large shape deformation is shown in photodeformable crosslinked liquid crystal polymer through the orientation change of liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Shape memory arrays that consist of repeat units such as cylinders, cuboids, prisms, cones, and polyhedral can be fabricated by silica molding, nanoindentation, or localized laser [ 208 ] ( Figure a). Altering the arrangement and intervals of the repeat SMP units will significantly affect SMP topography.…”
Section: Recent Advances In Applications Of Smps and Smpcsmentioning
confidence: 99%
“…Shape memory arrays that consist of repeat units such as cylinders, cuboids, prisms, cones, and polyhedral can be fabricated by silica molding, nanoindentation, or localized laser [ 208 ] ( Figure a). Altering the arrangement and intervals of the repeat SMP units will significantly affect SMP topography.…”
Section: Recent Advances In Applications Of Smps and Smpcsmentioning
confidence: 99%
“…Layer‐by‐layer stacking [ 8,16,17 ] and hybrid self‐assembly [ 18,19 ] show high lateral resolutions but are compromised by the complicated alignments and the lack of addressability. Direct writing technologies, such as laser writing, [ 20,21 ] and 3D printing [ 9,22,23 ] are currently only true 3D fabrication techniques but available for the very limited choice of materials and its resolution is optical‐diffraction limited. Focused ion beam [ 24,25 ] combines the high‐resolution and addressability together but is in short of controllability on 3D metastructures.…”
Section: Figurementioning
confidence: 99%
“…The In 2018, Y. Zhang et al reported a microscale local morphology with a reversible structure was produced by using a uniform, low-cost shape memory polystyrene film, which assisted a sensible controlled femtosecond laser scanning strategy to achieve symmetric and asymmetric growth. The structure had potential applications in particle capture/release and information encryption [114]. Shrinkage properties of polystyrene film was showed in Figure 8d.…”
Section: Large Area Micro/nano Structure Arraysmentioning
confidence: 99%
“…(e,f) SEM of polystyrene film after laser machining. (a-c) reproduced with permission from[113], Nature, 2017; and (d-f) reproduced with permission from[114],Wiley, 2018.…”
mentioning
confidence: 99%